1996
DOI: 10.1111/j.1365-2621.1996.tb14176.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Disulfide Bond in α‐Lactalbumin Infiuences Heat‐ Induced Gelation of α‐Lactalbumin‐Ovalbumin‐Mixed Gels

Abstract: The gel strength of ovalbumin mixed with ␣-lactalbumin (␣-La) was determined after heating at 80ЊC for 15 min at pH 7.0 Gel strength of the mixture of 4% ␣-La and 4% ovalbumin was two times that of 8% ovalbumin. Modified ␣-La at Cys6-Cys120 (3 SS␣-La) had low enhancement effects on ovalbumin gelation. Competitive ELISA using monoclonal antibody to ␣-La showed decreased binding reactivities after heating ␣-La with ovalbumin at specific concentrations. The decrease of total SH groups in the gel mixed with 3SS ␣-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The decreased accessibility of the disulfide bond will prohibit disulfide cross-linking during gelation. Legowo et al (40) observed that the addition of R-lac, a protein containing four disulfide bonds, significantly increased the hardness of heatset ovalbumin gels. This also confirms that the thiol group of ovalbumin is available for reaction and that the disulfide bonds in R-lac are accessible for reaction with the heat-exposed thiol groups of ovalbumin, in contrast to the one in ovalbumin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased accessibility of the disulfide bond will prohibit disulfide cross-linking during gelation. Legowo et al (40) observed that the addition of R-lac, a protein containing four disulfide bonds, significantly increased the hardness of heatset ovalbumin gels. This also confirms that the thiol group of ovalbumin is available for reaction and that the disulfide bonds in R-lac are accessible for reaction with the heat-exposed thiol groups of ovalbumin, in contrast to the one in ovalbumin.…”
Section: Resultsmentioning
confidence: 99%
“…This also confirms that the thiol group of ovalbumin is available for reaction and that the disulfide bonds in R-lac are accessible for reaction with the heat-exposed thiol groups of ovalbumin, in contrast to the one in ovalbumin. Indeed, Legowa et al (40) demonstrated the contribution of the Cys6-Cys120 disulfide bond of R-lac in the interaction between R-lac and ovalbumin. Note that WPI is a mixture of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, the MG‐like α‐La and reactive BSA can associate with each other to form irreversible complexes via hydrophobic bonding. Further heating may result in the formation of an adduct between these 2 whey proteins via a –SH/S–S bond interchange reaction, thus making a free –SH group available from the α‐La molecule (Cys6 or Cys120) (Legowo and others ). Additionally, 2 possible alternative reactions may occur after the formation of the reactive adduct.…”
Section: The Mechanism Of Whey Protein Aggregationmentioning
confidence: 99%
“…This free thiol may react with BSA via -SH/S-S interchange reaction and form dimer, trimer, and so on. Free thiol of BSA may also involve in -SH/S-S interchange reaction with Cys6 or Cys120 of α -lactalbumin [ 34 , 35 ]. In a mix solution, BSA is more effective than β -lactoglobulin to react with α -lactalbumin because a more covalent disulfide bond is formed between BSA/ α -La than β -Lg/ α -La combination [ 19 , 34 ].…”
Section: Whey Protein-casein Complex Formation In Heated Milkmentioning
confidence: 99%